Veronica Vierya COVID-19 Narrative - Vieyra, Veronica::::::::: (2022)
Veronica Vieyra's reflections on experiences during the COVID-19 pandemic with online classes, trying to visit family while in foster care, and working from home to support youth in foster care with gaining access to resources.